ANALISIS PENGARUH INVESTASI, LIKUIDITAS, PROFITABILITAS, UKURAN PERUSAHAAN, DAN PERTUMBUHAN PERUSAHAAN TERHADAP DIVIDEN PAYOUT RATIO PADA PERUSAHAAN SEKTOR INDUSTRI BARANG KONSUMSI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Dewi, Marlindasari; Sulistiyani, Tina (Jurnal Fokus Manajemen Bisnis, 2013)
This research is aimed to test five independent variables of Investments (Total Assets), Liquidity (Current Ratio, Profitability (Return On Assets), Corporate Size (Size) and Corporate Growth (Growth) wich are estimated to affect the dependent variables i.e. Dividend Payout Ratio of companies in consumer goods industrial sector listed on Indonesia Stock Exchange (IDX) in the year 2009-2012. The population in this research was the companies in consumer goods industrial sector listed on Indonesia Stock Exchange (IDX) in the year 2009-2012. The method in this research used purposive sampling. From the population of 38 companies, those became samples were 14 companies only. The analytical tool used was multipled linier regressions by using T-test (partially). The result of this research with Â = 5%, partially shows that the independent variables of Liquidity (CR), Corporate Size (Size), Corporate Growth (Growth) significantly affect the Dividend Payout Ratio where the significance value is smaller than Â = 5%, while the variables of Investment (TA) and Probability (ROA) do not have significant effect on Dividend Payout Ratio where the significance value is greater than =5%.